2014
DOI: 10.1179/1743289814y.0000000095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two types of layered silicate on mechanical and barrier properties of hydrogenated acrylonitrile butadiene rubber (HNBR)/layered silicate nanocomposites

Abstract: The role of the type of layered silicate platelets, OMMT and rectorite on the mechanical properties, aging resistance and oxygen permeation properties of HNBR/layered silicate nanocomposites was investigated. The effect of peroxide vulcanising agent on the dispersion of layered silicate in the HNBR matrix was also studied. HNBR was mechanically mixed with layered silicate via melt blending method. The results of the test show remarkable improvement in tensile strength, tear strength, aging resistance and oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It was revealed that the multiphase hybrid filler was able to preserve as well as showed process synergising effect in polymers and elastomers due to the compatibility and co‐operative interactions at the nanoscale. For example, Hybrid filler systems containing CB and carbon nanotube (CNT) ,CB and nanoclay and CB and nanographene/graphene oxide were developed and the resulting rubber nanocomposites demonstrated remarkable improvement in properties taken for their studies.…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that the multiphase hybrid filler was able to preserve as well as showed process synergising effect in polymers and elastomers due to the compatibility and co‐operative interactions at the nanoscale. For example, Hybrid filler systems containing CB and carbon nanotube (CNT) ,CB and nanoclay and CB and nanographene/graphene oxide were developed and the resulting rubber nanocomposites demonstrated remarkable improvement in properties taken for their studies.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its two‐dimensional structure, layered clay has good reinforcement effects in mechanical properties. [ 11,12 ] In addition, it could also improve the barrier properties, [ 13,14 ] heat resistance, [ 15,16 ] aging resistance, [ 17 ] flame retardancy, [ 18,19 ] electrical conductivity, [ 20 ] optical properties, and biodegradability of rubber. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%